A leitura das histórias em quadrinhos nas aulas de língua portuguesa: prerrogativas deste gênero multimodal - Monteiro, Reginaldo do Rego (2016)
The teaching of the Portuguese Language should enable the student to know the role of language, based on the diversity of texts that circulate socially. In this sense, we have as main objective to develop the reading and the comprehension of the comic genre, in order to consolidate oral and written skills and competences, allowing the discussion of the themes verified in the discourses present in this genre. The practice of reading should occupy a central place in school life, since in all disciplines there are tasks with texts - and it is essential to understand these texts. For this reason, it is necessary for the Portuguese-language teacher to adopt reading strategies that allow literacy to become fully effective in the student's life, so that this is an act of pleasure and requisite for social and social emancipation. Promotion of citizenship. Reading strategies imply deliberate choices, clear goals, and a project of building knowledge and seeking and producing information to satisfy the need to know. These strategies aim mainly at reading comprehension and meaningful learning through interaction with the most varied genres. Our research is based on studies by authors such as Bakhtin (2003, 2006), Eisner (1999, 2008), Marcuschi (2008), McCloud (2005, 2006, 2008) Kleiman (2004), Koch (2002, 2014), Ramos (2014), Solé (2008), Vergueiro (2013) and others, which bring to work with genres valuable and fundamental contribution. Thus, the methodological procedures adopted to carry out our work focused on bibliographic research, based on the basic sequence proposed by Cosson (2014). For the work with the present research, classroom readings and data collections were carried out in situational contexts of mother tongue teaching. Finally, we were able to promote literary literacy in our students through a work that involved reading, writing and orality. We investigated the relevance of comics in Portuguese language classes, encouraging, guiding, encouraging the student to find aspects related to fruition and above all to the strategies of sense formation, enabling him to make analogies and inferences, so that he could establish , With propriety, its reading competence.